Implementation of School Rules and Punishment for Students Who Violate it at SMK Negeri 2 Pagaralam - Runtah Widianti; Heriyah Oktaviani (Journal on Education, 2024)
The implementation of punishment in schools does not always yield the desired results and can lead to negative impacts if not managed wisely. Some violations of school regulations, such as tardiness, absenteeism, or deviant behavior, require appropriate approaches to ensure that the learning process is not disrupted and students can grow into responsible individuals. Sometimes, the punishment system tends to focus on sanctions without providing constructive guidance alternatives, which can hinder students' positive development. This study aims to investigate the implementation of school regulations such as tardiness, non-uniform attire, mandatory uniform attire, and absence/leaving during class hours/early departure. And the punishments given to students who violate these regulations at SMK Negeri 2 Pagar Alam. The type of research used is qualitative research, employing a descriptive analytical approach. Data collection techniques include observation, documentation, interviews, and the results obtained from the implementation of school regulations and punishments certainly have a significant impact on the formation of student discipline with binding rules. Familiarizing oneself with the school rules at SMK Negeri 2 Pagar Alam is done through habituation and socialization to students. The culture of SMK Negeri 2 Pagar Alam students in implementing school regulations is carried out through morning greetings, "ant operations," and school environmental patrols.